Мовленнєві тактики реалізації стратегії дискредитації в дискурсі дипломатів США - Судус, Юлія; Sudus, Yuliia; Sudus, Yulia (My University, 2018)
The paper is focused on the study of the discrediting strategy, which is a linguistic and pragmatic feature of contemporary U.S. diplomatic discourse, namely, to speech tactics that contribute to its implementation in the discourse of the U.S. diplomats. Attention is drawn to the US diplomats’ speeches by V. Nuland, D. Baer, G. Pyatt and S. Power made in 2013 – 2015, and related to the military conflict in the eastern Ukraine. The object of the study is the U.S. diplomatic discourse, which contains speech tactics of discrediting strategy. The subject matter is the tactics of the U.S. diplomats aimed at implementing the discrediting strategy in their speeches on the eve of military conflict in the eastern Ukraine and during the phases of its aggravation. As it was revealed, discrediting strategy is one of the most powerful conflict strategies of the U.S. diplomats’ verbal behavior, which is implemented in their discourse by means of such tactics as: accusation, impersonal accusation, disclosure, “universal truth”, condemnation, threat, order, mentioning in a negative light, and contrast. Among the leading linguistic tactics of implementing the discrediting strategy in the U.S. diplomatic discourse are tactics of mentioning in a negative light and accusation. Статтю присвячено дослідженню стратегії дискредитації, що є специ-фічною лінгвопрагматичною характеристикою сучасного англомовного дипломатичного дискурсу, а саме мовленнєвим тактикам, що сприяють її реалізації в дискурсі дипломатів США, зокрема в промовах чотирьох американських дипломатів – Саманти Пауер, Вікторії Нуланд, Джеффрі Пайєтта та Деніела Байєра – стосовно військового конфлікту на сході України, виголошених упродовж 2013–2015 рр. У чотирьох досліджуваних мовців, ос-новними виявились дві тактики: тактика згадування в негативному світлі та звинувачення, які найповніше та найчастотніше реалізують стратегію дискредитації в мовленні дипломатів переважно через прямі асертивні мовленнєві акти, що безумовно свідчить про стверджувальний характер мовлення в текстах промов усіх чотирьох дипломатів. Відтак встановлено, що провідними мовленнєвими тактиками реалізації стратегії дискредитації в англомовному дипломатичному дискурсі є тактики згадування в негативному світлі та звинувачення. Ці мовленнєві тактики реалізуються в англомовному дипломатичному дискурсі прямими асертивними мовленнєвими актами, а також їм притаманні певні лінгвальні маркери.
Speech Tactics of Discrediting Strategy in the U.S. Diplomatic Discourse
Keywords: англомовний дипломатичний дискурс; дипломатична промова; стратегія дискредитації; мовленнєві тактики; мовленнєві акти; лінгвальні маркери; U.S. diplomatic discourse; diplomatic speech; discrediting strategy; speech tactics; speech acts; linguistic markers